ESG and FinTech: Are they connected? - Galeone, Graziana; Ranaldo, Simona; Fusco, Antonio (Research in international business and finance, 2024)
Due to the growing focus of institutional investors on sustainability, investment decisions in the financial sector are increasingly focused on environmental, social and governance (ESG) aspects. In this scenario, together with technological progress, sustainable finance, unlike traditional finance, directs capital towards operations that generate positive impacts for the environment and society. FinTech, considered an accelerator of sustainable economic growth, is part of the technological innovations related to sustainable finance. Through the analysis of an exploratory case study of international importance, represented by the bank BNP Paribas, this article uses the unified theory of acceptance and use of technology (UTAUT) to investigate the factors that influence technological innovation in the banking sector. The results show that social influence, reinforced by ESG factors, is a variable that encourages technology adoption in the banking sector. Collaborations with FinTech companies support banks in achieving sustainability objectives more efficiently. This study makes an important contribution to the academic literature. It expands knowledge on the determinants of financial technology diffusion by analysing the effect of ESG factors not considered in previous literature. The study also presents practical implications for banks and policy makers. It is appropriate for banks to plan training activities for managers and employees on FinTech to promote understanding of these subjects and facilitate better institutionalization of sustainability practices. [Display omitted] •Extension of the literature exploring the relationship between FinTech and sustainability in the banking sector: studies addressing the relationship between Fintech and sustainability are limited, as it is an emerging topic and still being explored (Liu et al., 2022).•Revisiting the Unified Theory of Acceptance and Use of Technology (UTAUT), identifying a new factor that can influence the acceptance and implementation of technology in the banking sector.•Important practical implications: from internally analyzed relevant case studies, it emerged, on the one hand, that sustainability is not influenced by technology since the bank's choice to follow sustainability principles is solely related to its inclination toward these issues; on the other hand, the choice to operate according to these principles encouraged the use of forms of collaborations with FinTech, which were considered useful in achieving sustainability goals more quickly and efficiently.